Murder Ballads and Death in Song. Issue 1 (2nd January 2020) - Newman, Daniel
Abstract: This paper develops a typology of murder ballads to inform and assist legal scholars in engaging with this form of literature. Murder ballads are songs about death and killing, originating in seventeenth-century Europe thereon forming the bedrock of American folk, blues and country music from around the late nineteenth century onwards. This is a sub-genre of music explicitly focused on murder and, as such, presents a form of popular culture of great relevance to legal scholars, especially those with an interest in crime and justice. To date, legal scholarship has not given proper attention to murder ballads despite the vibrancy of the law and literature movement. This paper offers a call to rectify this dearth, following the law in literature approach of gaining insight into the human condition that can thereon be used to improve understanding of how law and society interact. The paper draws out a central theme of these murder ballads that speaks to a strong gender role in the narrative; violence against women. The ramifications of the normalisation of killing women that occurs in these traditional songs should be further developed to help understand the foundational role such cultural messages may have exerted on wider society.